THE EFFECT OF HOTEL ROOM RENTAL PRICES ON INCOME IN THE HOTEL SUB-SECTOR LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE PERIOD 2019-2023 - Sri Wahyuni Mustapa; Tri Handayani Amaliah; Hartati Tuli (PT. Jurnal Center Indonesia Publisher, 2025)
This study aims to analyze the Effect of Hotel Room Rental Prices on Revenue in the Hospitality Sub-Sector Listed on the Indonesia Stock Exchange for the 2019-2023 Period using quantitative methods. The sampling method used is purposive sampling with a total sample of 15 companies during the 5-year observation period, resulting in a total of 75 samples. The data analysis technique in this study uses SPSS 18. The results of this study indicate that room rental prices do not have a significant effect on revenue.